2022
DOI: 10.2147/ppa.s346171
|View full text |Cite
|
Sign up to set email alerts
|

Accepting Immunotherapy After Multiline Treatment Failure: An Exploration of the Anxiety and Depression in Patients with Advanced Cancer Experience

Abstract: Background: Tumor immunotherapy is a promising therapeutic strategy for patients with advanced cancers, and some tumors have profound and durable tumor regression. However, immunotherapy is still in the clinical trial stage with elusive long-term effects and complications as a new strategy. It is unclear whether patients possess an accurate understanding of the clinical benefits associated with these agents. Objective: To investigate the anxiety and depression of patients with advanced cancer who received immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Approximately one-fifth of patients in previous studies were found to have anxiety, while the proportion of anxiety in esophageal cancer patients found in previous studies was even higher, accounting for as much as one-fourth or more [ 32 , 33 ]. One possible reason for this difference is that our study did not include late-stage patients who were no longer eligible for surgery, while late-stage cancer patients often have a shorter survival time, more obvious symptoms, and are more likely to experience anxiety [ 34 36 ]. Another possible reason is that different cultural backgrounds may lead to differences in the perception of emotional states.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one-fifth of patients in previous studies were found to have anxiety, while the proportion of anxiety in esophageal cancer patients found in previous studies was even higher, accounting for as much as one-fourth or more [ 32 , 33 ]. One possible reason for this difference is that our study did not include late-stage patients who were no longer eligible for surgery, while late-stage cancer patients often have a shorter survival time, more obvious symptoms, and are more likely to experience anxiety [ 34 36 ]. Another possible reason is that different cultural backgrounds may lead to differences in the perception of emotional states.…”
Section: Discussionmentioning
confidence: 99%
“… 16 While our review did not identify any evidence that checkpoint inhibitors impacted mental health, a recent study reported that patients with multi-line treatment failure are susceptible to anxiety and depression during immunotherapy because of emotional vulnerability due to stressors such as long-term suffering, high financial burden, and low self-healing expectations. 74 Future qualitative studies of immunotherapy should examine the impact of receiving immunotherapy both on physical function and mental health, as important components of patient QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The Dr (medical oncologist) came in, and he asked if everything (about immunotherapy) had been explained to us and were we aware of all the side effects, we ran through it all again … they gave us some paperwork to read as well. (Livingstone et al, To bridge perceived knowledge gaps, some individuals sought further information about ICIs and irAEs from the internet, friends, family and peer support groups (Hou et al, 2023;Jamieson et al, 2020;Livingstone et al, 2021;Park et al, 2020;Xie et al, 2022). Some individuals; however, found peer support groups were often inadequate (Park et al, 2020).…”
Section: Information Provision and Preferencesmentioning
confidence: 99%
“…(Hou et al, 2023, p. 497-498) ICIs were generally perceived as less toxic than chemotherapy with some individuals reporting feeling well between treatments (Levy et al, 2019) and being able to resume activities relatively quickly following treatment (Bharmal et al, 2018;Cheung et al, 2019;Park et al, 2020;Shuk et al, 2017). Lambert et al, 2020;Milne et al, 2020;Park et al, 2020;Shuk et al, 2017;Xie et al, 2022).…”
Section: The Experience and Impact Of Ici Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation